2017
DOI: 10.20396/bjos.v15i3.8649984
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Impact Profile (OHIP-14) and its association with dental treatment needs of adolescents in a rural Nigerian community

Abstract: Aim: To validate and determine the applicability of OHIP-14 in assessing the impact of unmet dental treatment needs on the quality of life of adolescents in a rural community. Methods: The OHIP-14 questionnaire and the Aesthetic component (AC) of Index of Orthodontic Treatment Need (IOTN) were data collection instruments in a cross sectional survey among students in a rural community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Viiti R et al, also reported similar findings. 23 Low BMI had higher impact on oral health related quality of life. Underweight adolescents reported to have higher OHIP scores implying poorer quality of life.…”
Section: Discussionmentioning
confidence: 93%
“…Viiti R et al, also reported similar findings. 23 Low BMI had higher impact on oral health related quality of life. Underweight adolescents reported to have higher OHIP scores implying poorer quality of life.…”
Section: Discussionmentioning
confidence: 93%
“…And as exclusion criteria those university students who perhaps failed to complete the questionnaire responses. As this is a research using the survey method, the research instrument is a questionnaire based on the study by França (2019), Albuquerque et al (2019), Vitti et al (2011) and Alvarenga et al (2011), thus the form was made available to participants through the Google Forms Platform through the link to access the survey and respond. The questionnaire is entitled Research on Hygiene Habits with Oral Health and Knowledge of University Students regarding Oral Pathologies, consisting of 25 questions, divided into 6 (six) sections that correspond to the research structure: TCLE validation; participant profile; Self-perception; behavioral habits; orality issues; and finally, thanks.…”
Section: Methodsmentioning
confidence: 99%
“…The responses are scored on a Likert scale having five points which are from never to very often. OHIP-14 has been used in the Pakistani population by Ibrahim Warsi et al in Karachi 6,7 .…”
Section: Introductionmentioning
confidence: 99%